BACTERIAL INDICES OF BROILER CHICKEN SLAUGHTER PRODUCTS WHEN RATION IS ENRICHED BY NANOMICROELEMENT FEED ADDITIVE «MICROSTIMULIN» IN VETERINARY AND SANITARY INSPECTION ASPECT - Яценко, І. В.; Кириченко, В. М. (Scientific Progress & Innovations, 2015)
The bacterial contamination of broiler chicken slaughter products (white and red muscles, heart, liver, muscular stomach) by conditionally pathogenic and pathogenic microorganisms when the ration of the chickens was enriched by nanomicroelement feed additive (NMFA) «Microstimulin» for four days of storage at 0–4 ºC has been analyzed. It has been found out that the lowest level of MAFAnM, BGIR, bacteria Proteus in all slaughter products under investigation was registered in the 3rd experimental group the broiler chickens of which were given 20 cm³/dm³ NMFA «Microstimulin» with water. The highest level of MAFAnM, BGIR, bacteria Proteus was registered in the control group the broiler chickens which were not given NMFA «Microstimulin» with water. The dependence between the dose of NMFA «Microstimulin» and the number of microorganisms in the products of slaughtering has been proved.